Asialoglycoprotein receptor targeted delivery of doxorubicin nanoparticles for hepatocellular carcinoma - Sandhya Pranatharthiharan; Mitesh D. Patel; Vinod C. Malshe; Vaishali Pujari; Ajit Gorakshakar; Manisha Madkaikar; Kanjaksha Ghosh; Padma V. Devarajan (Taylor & Francis Group, 2017)
We report asialoglycoprotein receptor (ASGPR)-targeted doxorubicin hydrochloride (Dox) nanoparticles (NPs) for hepatocellular carcinoma (HCC). Polyethylene sebacate (PES)-Gantrez® AN 119 Dox NPs of average size 220 nm with PDI < 0.62 and ∼20% Dox loading were prepared by modified nanoprecipitation. ASGPR ligands, pullulan (Pul), arabinogalactan (AGn), and the combination (Pul-AGn), were anchored by adsorption. Ligand anchoring enabled high liver uptake with a remarkable hepatocyte:nonparenchymal cell ratio of 85:15. Furthermore, Pul-AGn NPs exhibited an additive effect implying incredibly high hepatocyte accumulation. Galactose-mediated competitive inhibition confirmed ASGPR-mediated uptake of ligand-anchored NPs in HepG2 cell lines. Subacute toxicity in rats confirmed the safety of the NP groups. However, histopathological evaluation suggested mild renal toxicity of AGn. Pul NPs revealed sustained reduction in tumor volume in PLC/PRF/5 liver tumor-bearing Nod/Scid mice up to 46 days. Extensive tumor necrosis, reduced collagen content, reduction in the HCC biomarker serum α-fetoprotein (p < 0.05), a mitotic index of 1.135 (day 46), and tumor treated/tumor control (T/C) values of <0.42 signified superior efficacy of Pul NPs. Furthermore, weight gain in the NP groups, and no histopathological alterations indicated that they were well tolerated by the mice. The high efficacy coupled with greater safety portrayed Pul Dox NPs as a promising nanocarrier for improved therapy of HCC.